Utilization of Lateritic Soil as Coarse Aggregate in Concrete for Artificial Aquifer - Tonnayopas, Danupon; Janmart, Nattawat; Charoensuk, Nanthanat (RMUTL Engineering Journal, 2020)
This paper presents a laboratory study on the suitability of using lateritic soil as coarse aggregate in pervious concretes as artificial aquifer. Two sizes of laterite available in Prince of Songkla University Hat Yai campus, 9.5-25.0 mm and 25.0-37.5 mm in size, were used as the coarse aggregates. The mixture contained ordinary Portland cement Type 1 (OPC), lateritic aggregate, and sand in proportion of 1:2:1.25 by weight and the OPC was partially replaced with ground rice husk ash in proportion of 15wt.%. All of the samples were casted in size of 100×100×100 mm and the bulk density, water absorption, Infiltration rate, Shore hardness and compressive strength after curing for 1, 7 and 28 days were determined. The mineral phases and microstructure were analyzed via X-ray diffraction (XRD) and scanning electron microscope (SEM) techniques, respectively. Experimental results showed that the laterite coarse aggregate of size 25.0-9.5 mm and concrete cured for 28 days provided compressive strength of 18 MPa, water absorption of 30.57% and infiltration rate of 0.15-0.37 m3/min/m2. The XRD pattern revealed mineral phases abundant of ettringite and calcite. SEM displays interfacial transition zone. The lateritic aggregate concrete was found to be a satisfactorily shallow artificial unconfined aquifer.